Factor Inputs and Japanese Manufacturing Trade Structure - Urata, Shujiro (The Review of Economics and Statistics, 1983)
The Japanese international trade structure in manufactured goods has been analyzed using cross-section regression analysis in which labor, capital, human capital, and energy are regressed on Japanese net exports, exports and imports with the world, OECD and developing countries for 1967 and 1975. Skill and wage differential measures have been utilized for the measuring of human capital. Contrary to the dualism found in earlier studies, the estimated results show that in 1967 Japan exported unskilled labor intensive goods with respect to the developing countries as well as the OECD countries. In 1975 Japan exported capital intensive goods to all regions and imported unskilled labor intensive goods from the world and the developing countries. Skilled labor intensive goods were imported from the OECD countries in both years. Drastic changes between 1967 and 1975 are noted. Japanese exports shifted from unskilled labor intensive goods to capital intensive goods while imports did the opposite. This result conforms to the changes in unskilled labor and capital usage in Japan and her major trading partners.